DAGESTAN’S UNIONS OF RURAL COMMUNITIES: FORMATION, ETHNIC STRUCTURE, GOVERNANCE SYSTEM - Aliev, Bagomed Gadaevic (History, Archeology and Ethnography of the Caucasus, 2024)
The unions of rural communities (URCs) of Dagestan were self-governing structures that united villages (jamaats), serving as a key component in the political organization of the Dagestani peoples. The primary functions of the URC encompassed a broad range of life support activities, including material, demographic, and spiritual reproduction, the continuity of generations, territorial protection, and maintaining independence. The ethnic factor played a nominal role in the URC formation, which primarily consisted of subethnic groups or unions of jamaats that shared specific dialects of a specific people. The governing bodies of URCs were established and located in the main villages, with a governance system that was generally uniform across Dagestani community unions. However, the URC governance system was unique in that its governing bodies typically functioned as the central villages’ governing bodies. While rural community residents did not directly participate in electing senior officials, they delegated representatives to all-union gatherings such as people’s assemblies and councils of elders. The highest administrative officials, including elders and qadis, of the central settlements were elected exclusively by residents of these settlements, despite their authority extending over the entire union of rural communities. The roles and responsibilities of these officials were meticulously detailed and strictly adhered to. URCs in Dagestan, documented since the Early Middle Ages, represent a new stage in socio-political self-organization, socio-cultural dynamics, and the formation of civil identity within the Dagestani multi-ethnic community, succeeding the emergence of large rural settlements (“shi,” “roso,” “khyur,” etc.).